Narrative skills of children with developmental language disorder: retelling in macrostructure - Andreou, Georgia; Lemoni, Garyfallia (Frontiers in Education, 2025)
IntroductionDevelopmental Language Disorder is a common developmental disorder that affects 7% of both preschool and school-aged children. Children with DLD typically demonstrate simpler syntax, higher rates of grammatical errors and greater difficulty acquiring new vocabulary in comparison to typically developing (TD) children. Research has shown that children with DLD have significant language difficulties that result in poor narrative performance.MethodsIn this paper, the narrative skills of monolingual children with DLD and typically developing (TD) children are examined at the macrostructural level, using one of the most common methods of assessing narrative skills, picture retelling. The sample consists of 100 preschool and school-aged children (50 with DLD and 50 TD), aged 5 to 11 years, who were matched according to chronological age, socioeconomic status and language input received at home. The parameters measured are story structure, structural complexity and Internal State Terms (IST). The research hypotheses of the study were: (a) Children with DLD will present lower performance than TD children in the parameter of story structure, (b) Children with DLD are expected to present lower performance than TD children in the parameter of structural complexity, (c) Children with DLD will present lower performance than TD children in the parameter of expressing Internal State Terms and (d) There will be a significant dependence between the groups (children with DLD and TD children) and the subcategories of the story structure.ResultsThe results confirmed all the above hypotheses except for the hypothesis that there is a significant dependence between the groups of children in the subcategories of the story structure.DiscussionThe findings of our study revealed that the narratives skills of children with DLD are more affected at the level of macrostructure than those of children with Typical Development (TD). However, a significant dependence between the groups (children with DLD and TD children) and the subcategories of the story structure was found only in five out of sixteen components in the three episodes of the story, a finding which is discussed on the basis of the limitations included in the present study.